Episodes. The complete first season & second seasons [videorecording (DVD)] - LeBlanc, Matt; Mangan, Stephen; Greig, Tamsin, 1967-; Pankow, John (CBS DVD, 2013)
When a British husband-and-wife writing team gets the opportunity to bring their successful TV series across the pond, they soon discover that making it big in America means changing nearly everything about the show. As their star actor, Matt, wreaks havoc on their script and their marriage, the duo tries to keep it all under control as they deal with awkward Hollywood funerals, falling ratings, celebrity stalkers and the even more intense drama that happens off- camera. Tune in for all the laughs in this titillating and timely send-up of Tinseltown.